2022
DOI: 10.3390/cancers14102386
|View full text |Cite
|
Sign up to set email alerts
|

The Proportion of Occupationally Related Cholangiocarcinoma: A Tertiary Hospital Study in Northeastern Thailand

Abstract: Northeastern Thailand registers the highest worldwide incidence of cholangiocarcinoma (CCA). Most of the cases are associated with liver flukes, while unknown causes comprise approximately 10–30% of cases, and these could be due to occupational exposures. Our aim was to determine the magnitude of occupational causes of CCA in a tertiary hospital in northeastern Thailand. We conducted a cross-sectional study with a sample of 220 patients between March and November 2021. Descriptive statistics were used to analy… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1

Citation Types

0
2
0

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(2 citation statements)
references
References 39 publications
0
2
0
Order By: Relevance
“…Notably, it was observed that iCCA incidence increased with cumulative exposure to 1,2-DCP (adjusted RR = 14.9, 95% CI 4.1-54.3 for middle-exposure category, and adjusted RR = 17.1, 95% CI 3.8-76.2 for high-exposure category), suggesting an exposure-response relationship [70]. The potential association between CCA development and 1,2-DCP and/or DCM exposure has been reinforced by further epidemiological studies reporting the occurrence of this malignancy in an additional 13 printing workers of other Japanese companies [71,72] and in 6 out of 11 Thai workers occupationally exposed to these substances [73].…”
Section: Organic Solventsmentioning
confidence: 95%
See 1 more Smart Citation
“…Notably, it was observed that iCCA incidence increased with cumulative exposure to 1,2-DCP (adjusted RR = 14.9, 95% CI 4.1-54.3 for middle-exposure category, and adjusted RR = 17.1, 95% CI 3.8-76.2 for high-exposure category), suggesting an exposure-response relationship [70]. The potential association between CCA development and 1,2-DCP and/or DCM exposure has been reinforced by further epidemiological studies reporting the occurrence of this malignancy in an additional 13 printing workers of other Japanese companies [71,72] and in 6 out of 11 Thai workers occupationally exposed to these substances [73].…”
Section: Organic Solventsmentioning
confidence: 95%
“…Similarly, a second study nested in the Nordic Occupational Cancer (NOCCA) cohort and including 5430 CCA cases, reported an increased risk of CCA in subjects exposed to asbestos, with a stronger association for iCCA than eCCA [82]. More recently, a cross-sectional study in Thai CCA patients reported that 11 (5.5%) out of 200 cases had a possible occupational cause, with 6 (54.5%) cases related to asbestos exposure [73].…”
Section: Asbestosmentioning
confidence: 96%